2011
DOI: 10.1158/0008-5472.can-10-3761
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D3 Sensitizes RAF Inhibitor RAF265 in Melanoma Cells by Preventing Reactivation of MAPK Signaling

Abstract: RAS mutations occur in more than 30% of all human cancers but efforts to directly target mutant RAS signaling as a cancer therapy have yet to succeed. As alternative strategies, RAF and MEK inhibitors have been developed to block oncogenic signaling downstream of RAS. As might be expected, studies of these inhibitors have indicated that tumors with RAS or BRAF mutations display resistance RAF or MEK inhibitors. In order to better understand the mechanistic basis for this resistance, we conducted a RNAi-based s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…45-3192); PKD2-2, 59-AAUGACCUUAACUGCCACGUCCCGG-39 (Azoitei et al, 2010); PKD3-1, 59-GAACGAGUCUUUGUAGUAAtt-39 (Silencer Selected Validated siRNA, catalog no. 4390824); PKD3-2, 59-GAAAGUUCCAC-ACACAUUU-39 (Chen et al, 2011); HDAC1, 59-CAGCGACUGUUUGAGAA-CCTT-39 and 59-CUAAUGAGCUUCCAUACAATT-39 (Senese et al, 2007).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…45-3192); PKD2-2, 59-AAUGACCUUAACUGCCACGUCCCGG-39 (Azoitei et al, 2010); PKD3-1, 59-GAACGAGUCUUUGUAGUAAtt-39 (Silencer Selected Validated siRNA, catalog no. 4390824); PKD3-2, 59-GAAAGUUCCAC-ACACAUUU-39 (Chen et al, 2011); HDAC1, 59-CAGCGACUGUUUGAGAA-CCTT-39 and 59-CUAAUGAGCUUCCAUACAATT-39 (Senese et al, 2007).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…In this instance, the siRNA knockdown of PRKD3 reduced the IC 50 of both RAF265 and vemurafenib in multiple melanoma cell lines and prevented the reactivation of MAPK signaling following drug treatment 89 . In BRAF V600E mutant cell lines lacking PTEN expression, PRKD3 activity further contributed to resistance through the reactivation of PI3K/AKT signaling following RAF inhibition 89 .…”
Section: Introductionmentioning
confidence: 86%
“…Other recent studies identified protein kinase D3 (PRKD3) as being a potential mediator of intrinsic resistance to the RAF inhibitors RAF265 and vemurafenib 89 (Figure 3). In this instance, the siRNA knockdown of PRKD3 reduced the IC 50 of both RAF265 and vemurafenib in multiple melanoma cell lines and prevented the reactivation of MAPK signaling following drug treatment 89 .…”
Section: Introductionmentioning
confidence: 99%
“…(86, 87) In preclinical studies, these agents had broad activity against both BRAF mutant and wild-type cell lines. (8691) Though there was some initial enthusiasm of sorafenib in combination with chemotherapy, it has been proven to be ineffective as a single-agent and in combination with chemotherapy in numerous phase I, II, and III trials. (9298) Additionally, RAF265 has been shown to be similarly ineffective.…”
Section: Molecular Signaling In Melanomamentioning
confidence: 99%